New extended generalized Kudryashov method for solving three nonlinear partial differential equations - Zayed, Elsayed M.E.; Shohib, Reham M.A.; Alngar, Mohamed E.M. (Nonlinear Analysis: Modelling and Control, 2020)
New extended generalized Kudryashov method is proposed in this paper for the first time. Many solitons and other solutions of three nonlinear partial differential equations (PDEs), namely, the (1+1)-dimensional improved perturbed nonlinear Schrödinger equation with anti-cubic nonlinearity, the (2+1)-dimensional Davey–Sterwatson (DS) equation and the (3+1)-dimensional modified Zakharov–Kuznetsov (mZK) equation of ion-acoustic waves in a magnetized plasma have been presented. Comparing our new results with the well-known results are given. Our results in this article emphasize that the used method gives a vast applicability for handling other nonlinear partial differential equations in mathematical physics.
Keywords: solitary solutions; a new extended generalized Kudryashov method; the improved perturbed nonlinear Schrödinger equation with anti-cubic nonlinearity; Davey–Sterwatson (DS) equation; the modified Zakharov–Kuznetsov (mZK) equation of ion-acoustic waves in a magnetized plasma